2017
DOI: 10.5604/01.3001.0013.7359
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ Przestępczości Innokulturowej Na Poczucie Bezpieczeństwa Obywateli Rp

Abstract: Postępujące procesy globalizacyjne powodują określone konsekwencje zarówno w sferze ekonomiczno-społecznej, jak i prawnej, co jest w ostatnich latach, w kontekście nowych zagrożeń, przedmiotem analizy nie tylko prawników czy socjologów, ale także kryminologów. Przestępczość innokulturowa jest również przedmiotem rosnącego zainteresowania instytucji odpowiedzialnych za bezpieczeństwo i porządek publiczny w krajach Unii Europejskiej. Jest to spowodowane między innymi swobodą przemieszczania pomiędzy krajami UE o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Obviously, our estimates depended on a number of assumptions described in preceding sections of this article, but we consider them to be rather conservative. For example, the daytime portion of drift was omitted in the present estimates; however, our studies performed in 2018-2019 indicated that diurnal drift constituted 0-13%, but in certain instances it was as much as 72% of nocturnal ELH densities (Mikołajczyk et al, 2020). Moreover, our sampling ended in mid-July when ELH were still drifting.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Obviously, our estimates depended on a number of assumptions described in preceding sections of this article, but we consider them to be rather conservative. For example, the daytime portion of drift was omitted in the present estimates; however, our studies performed in 2018-2019 indicated that diurnal drift constituted 0-13%, but in certain instances it was as much as 72% of nocturnal ELH densities (Mikołajczyk et al, 2020). Moreover, our sampling ended in mid-July when ELH were still drifting.…”
Section: Discussionmentioning
confidence: 85%
“…The present study is a continuation of research that has been conducted since 2018 on the impact three thermal power plants (Kozienice, Połaniec, and Ostrołęka) equipped with once-through cooling systems had on the Vistula and Narew river ecosystems (Mikołajczyk et al, 2020(Mikołajczyk et al, , 2022Cebula et al, 2021). Our previous studies were preliminary, and ELH sampling was less frequent (fortnightly or even longer intervals), and the organisms were not identified to the species but quantified en masse, which is why in 2022 we sampled drifting ELH more frequently and identified them using molecular methods.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation